Pengaruh Faktor-Faktor Fundamental Terhadap Nilai Perusahaan - Usemahu, Rasni Hanipa (ISAS, 2024)
The purpose of this research to determine the influence of investment decisions, funding decisions and profitability on company value. Case studies of real estate and property companies listed on the IDX in 2019-2022